LANDSCAPE ECOLOGICAL METHOD TO STUDY AGRICULTURAL VEGETATION: SOME EXAMPLES FROM THE PO VALLEY - GIGLIO, E. (Annali di Botanica, 2006)
Vegetation is the most important landscape component, as regards to its ability to catch solar energy and to transform it, but also to shape the landscape, to structure the space, to create the fit environment for different animal species, to contribute to the maintenance of a correct metastability level for the landscape, etc. It is a biological system which acts under the constraints of the principles of the System Theory and owns the same properties of any other living system: so, it is a complex adaptive, hierarchical, dynamic, dissipative, self-organizing, self-transcendent, autocatalytic, self-maintaining system and follows the non-equilibrium thermodynamic. Its ecological state can be investigated through the comparison between “gathered data” (pathology) and “normal data” (physiology) for analogous types of vegetation. The Biological Integrated School of Landscape Ecology provides an integrated methodology to define ecological threshold limits of the different Agricultural Landscape types and applies to agricultural vegetation the specific part of the new methodology already tested to studying forests (the Landscape Biological Survey of Vegetation). Ecological quality, better and worst parameters, biological territorial capacity of vegetated corridors, agricultural field, poplar groves, orchards and woody remnant patches are investigated. Some examples from diverse agricultural landscapes of the Po Valley will be discussed. KEY WORDS: agricultural landscape, vegetation, landscape ecology, landscape health, Biological Integrated Landscape Ecology, Landscape Biological Survey of vegetation.